Twentieth Century Borrowings from French to English : Their Reception and Development. - Schultz, Julia (Cambridge Scholars Pub., 2012)
French has long been the donor language par excellence in the history of English. French has contributed to the English vocabulary in the form of new words since before the Norman Conquest. The French influence on the English lexicon represents the focus of linguistic concern in a considerable number of investigations of the language and its development. Yet French borrowings which have recently been adopted into English have as yet figured little if at all in such studies. The present study ...